The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00442-004-1526-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an urban-rural CO 2 /temperature gradient and associated changes in initial plant productivity during secondary succession

Abstract: To examine the impact of climate change on vegetative productivity, we exposed fallow agricultural soil to an in situ temperature and CO 2 gradient between urban, suburban and rural areas in 2002. Along the gradient, average daytime CO 2 concentration increased by 21% and maximum (daytime) and minimum (nighttime) daily temperatures increased by 1.6 and 3.3°C, respectively in an urban relative to a rural location. Consistent location differences in soil temperature were also ascertained. No other consistent dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 16 publications
(19 reference statements)
4
82
0
Order By: Relevance
“…Measuring the gradient of carbon dioxide between urban and rural locations (e. g. Berry & Colls, 1990a/b;Ziska et al, 2004;George et al, 2007). All of these studies were carried out by stationary measurements.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Measuring the gradient of carbon dioxide between urban and rural locations (e. g. Berry & Colls, 1990a/b;Ziska et al, 2004;George et al, 2007). All of these studies were carried out by stationary measurements.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…exhaust (Lovett et al 2000), CO 2 levels are elevated (Pataki et al 2003;Ziska et al 2004), urban heat island effects cause warmer temperatures (Taha 1997), and exotic species propagules are at higher densities (Lonsdale 1999). Together, these variables can be thought of as an "urban influence", and they represent the future conditions all forests may experience as humans continue to modify the environment (Carreiro and Tripler 2005).…”
mentioning
confidence: 99%
“…For example, Gregg et al (2003) found that in urban areas (1) atmospheric CO 2 concentrations were up to 15% higher; (2) nitrogen deposition was significantly higher; (3) aerosol concentrations were up to 200% higher; and (4) tropospheric ozone levels were up to 40% lower. Additionally, the frost-free period (FFP) was at least several weeks longer at the urban Baltimore site than at the rural site (Ziska et al 2004). As noted in Gregg et al (2003), it is possible that there was no enhanced growth in urban areas; rather, suppressed growth in rural areas may have been caused by increased ozone exposure.…”
Section: Potential Impacts Of Urbanization On Nepmentioning
confidence: 99%
“…For first-year vegetation regrowth (e.g. lambsquarters Chenopodium album) on previously fallow land in the Baltimore (Maryland, USA) area, Ziska et al (2004) found that by the end of the growing season aboveground biomass at an urban site was 115% higher than that at a rural site. Similarly, Gregg et al (2003) 202 Diem et al: Urbanization and land -atmosphere carbon exchange reported that Eastern cottonwood Populus deltoides grown in urban areas in New York City had twice as much biomass as the same trees grown in nearby rural areas.…”
mentioning
confidence: 99%